Tracking Global Demand for Advanced Economy Sovereign Debt - Arslanalp, Serkan (IMF Working Papers; Working Paper, 2012)
Recent events have shown that sovereigns, just like banks, can be subject to runs, highlighting the importance of the investor base for their liabilities. This paper proposes a methodology for compiling internationally comparable estimates of investor holdings of sovereign debt. Based on this methodology, it introduces a dataset for 24 major advanced economies that can be used to track USD 42 trillion of sovereign debt holdings on a quarterly basis over 2004-11. While recent outflows from euro periphery countries have received wide attention, most sovereign borrowers have continued to increase reliance on foreign investors. This may have helped reduce borrowing costs, but it can imply higher refinancing risks going forward. Meanwhile, advanced economy banks' exposure to their own government debt has begun to increase across the board after the global financial crisis, strengthening sovereign-bank linkages. In light of these risks, the paper proposes a framework-sovereign funding shock scenarios (FSS)-to conduct forward-looking analysis to assess sovereigns' vulnerability to sudden investor outflows, which can be used along with standard debt sustainability analyses (DSA).a It also introduces two risk indices-investor base risk index (IRI) and foreign investor position index (FIPI)-to assess sovereigns' vulnerability to shifts in investor behavior.